Penalizacja propagowania ideologii : Uwagi na marginesie nowelizacji art. 256 k.k. - Urbańczyk, Michał (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The article delves into the interpretive and practical challenges arising from the incorporation of the term “ideology” within the Polish Penal Code, along with the introduction of a novel criminal offense pertaining to the dissemination of Nazi, communist, fascist ideologies, or ideologies that incite the use of violence for the purpose of influencing political or social life. Primarily, it will elucidate the complexities that may confront criminal courts and the involved parties when confronted with the necessity of applying the amended legal provisions. Subsequently, an effort will be undertaken to provide a structured exposition of the historical development of political and legal doctrines. This historical context may serve to ameliorate some of the uncertainties, or potentially serve as a persuasive element within legal proceedings. The article adopts a multifaceted approach, encompassing a dogmatic analysis, a linguistic examination, and a comparative legal methodology. The analysis culminates in the inference that the aforementioned amendment fails to introduce lucid and precisely defined concepts into the Penal Code, thereby contravening the fundamental legal principle of definiteness within criminal law provisions.
Keywords: totalitaryzm; ideologia; mowa nienawiści; wolność wypowiedzi; wolność słowa